Method for producing lithium cobalt pyrophosphate and method for producing solid-state battery
By controlling the temperature and water addition amount, mixing lithium compounds, cobaltium compounds and phosphate powders to prepare a uniform cobaltium pyrolinate, solving the problem of poor charge and discharge characteristics caused by different crystal phases, and achieving high-performance solid battery positive electrode active material.
Patent Information
- Application Number
- JP2020090477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-25
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-05-25
AI Technical Summary
In the production of cobaltium pyrolinate, different crystal phases of different crystal phases are easily generated, resulting in poor charging and discharging characteristics when used as the positive electrode active material of solid battery.
By controlling the temperature and the amount of water addition, the lithium compound, cobalt compound and phosphate powder are mixed to form a uniform precursor material and sintered at high temperature in a non-oxidizing atmosphere to prepare a uniform cobaltium pyrolinate.
Cobaltium pyrolinate with excellent charging and discharging characteristics was prepared for the positive electrode active substance of solid battery, which improved the performance of the battery.
Smart Images

Figure 0007624645000001 
Figure 0007624645000002 
Figure 0007624645000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing lithium cobalt pyrophosphate and a method for producing a solid-state battery. [Background technology]
[0002] A technology is known in which lithium cobalt pyrophosphate (Li2CoP2O7) is used as a positive electrode active material in solid-state batteries. As a method for producing lithium cobalt pyrophosphate, for example, a dry production process is known in which the raw materials are mixed and the mixed raw materials are calcined under predetermined conditions to obtain lithium cobalt pyrophosphate. In addition, a wet production process is known in which the raw materials are mixed with citric acid to obtain an aqueous solution, and the aqueous solution is dried to obtain a powder, which is calcined under predetermined conditions to obtain lithium cobalt pyrophosphate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-182949 A [Patent Document 2] JP 2019-149302 A Summary of the Invention [Problem to be solved by the invention]
[0004] It is known that in the production of lithium cobalt pyrophosphate, in addition to the desired crystalline phase of lithium cobalt pyrophosphate, a crystalline phase different from the desired crystalline phase (also called a "different phase") may be generated. The generation of such a different phase may cause inconvenience in using lithium cobalt pyrophosphate. For example, when lithium cobalt pyrophosphate is to be used as a positive electrode active material of a solid-state battery as described above, if the positive electrode active material contains a different phase different from lithium cobalt pyrophosphate, a solid-state battery exhibiting sufficient charge / discharge characteristics may not be obtained.
[0005] In one aspect, the present invention aims to provide lithium cobalt pyrophosphate in which the generation of a different phase is suppressed. [Means for solving the problem]
[0006] In one embodiment, the amount of lithium pyrophosphate based on the composition of the lithium pyrophosphate Lithium carbonate or lithium nitrate or lithium hydroxide , Basic cobalt carbonate or cobalt nitrate or cobalt hydroxide or cobalt oxide, and ammonium dihydrogen phosphate or ammonium monohydrogen phosphate or phosphoric acid The powder of Below 40℃ providing at a first temperature, 2.0% by weight to 38.3% by weight of the total weight of the powder A step of obtaining a powdered first material by gradually adding water and mixing the first material; 40℃~60℃ obtaining a powdered second material by mixing at a second temperature; drying the second material at a fourth temperature of 90° C.; The second material, In air or non-oxidizing atmosphere, 650℃~690℃ and calcining at a third temperature.
[0007] In one embodiment, the amount of lithium pyrophosphate based on the composition of lithium cobalt pyrophosphate Lithium carbonate or lithium nitrate or lithium hydroxide , Basic cobalt carbonate or cobalt nitrate or cobalt hydroxide or cobalt oxide, and ammonium dihydrogen phosphate or ammonium monohydrogen phosphate or phosphoric acid The powder of Below 40℃ Prepared at a first temperature, 40℃~60℃ At the second temperature 14.9% by weight to 95.8% by weight of the total weight of the powder A step of obtaining a powdered first material by gradually adding water and mixing; drying the first material at a fourth temperature of 90° C.; The first material, In air or non-oxidizing atmosphere, 650℃~690℃ and calcining at a third temperature.
[0008] Furthermore, in one embodiment, there is provided a method for producing a solid-state battery containing the lithium cobalt pyrophosphate produced as described above as a positive electrode active material. Effect of the Invention
[0009] In one aspect, it is possible to realize lithium cobalt pyrophosphate in which the formation of heterogeneous phases is suppressed. In addition, it is possible to realize a solid-state battery that contains lithium cobalt pyrophosphate in which the formation of heterogeneous phases is suppressed as a positive electrode active material and exhibits excellent charge / discharge characteristics. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a diagram illustrating a method for producing lithium cobalt pyrophosphate according to the first embodiment. [Diagram 2] FIG. 2 is a diagram showing an example of a method for producing lithium cobalt pyrophosphate according to the first embodiment. [Diagram 3] FIG. 4 is a diagram illustrating a method for producing lithium cobalt pyrophosphate according to a second embodiment. [Figure 4] FIG. 4 is a diagram showing an example of a method for producing lithium cobalt pyrophosphate according to the second embodiment. [Diagram 5] FIG. 1 is a diagram illustrating an example of a configuration of a solid-state battery. [Figure 6] FIG. 2 is a diagram (part 1) for explaining a first forming example of a solid-state battery main body. [Figure 7] FIG. 2 is a diagram (part 2) for explaining the first forming example of the solid-state battery main body. [Figure 8] FIG. 1 is a diagram (part 1) for explaining a second example of forming a solid-state battery main body. [Figure 9] FIG. 2 is a diagram (part 2) for explaining a second example of forming a solid-state battery main body. [Figure 10] FIG. 13 is a diagram (part 1) for explaining a third example of forming a solid-state battery main body. [Figure 11] FIG. 2 is a diagram (part 2) for explaining a third example of forming a solid-state battery main body. [Figure 12] FIG. 2 is a diagram illustrating the firing of the basic structure of a solid-state battery body. [Figure 13] FIG. 11 is a diagram showing another configuration example of a solid-state battery. [Figure 14] FIG. 13 is a diagram showing yet another configuration example of a solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [First embodiment] FIG. 1 is a diagram for explaining a method for producing lithium cobalt pyrophosphate according to a first embodiment.
[0012] In the manufacturing method of lithium cobalt pyrophosphate (Li2CoP2O7, hereinafter also referred to as "LCPO") shown in FIG. 1, first, powders of a lithium (Li) compound, a cobalt (Co) compound, and a phosphorus (P) compound in amounts based on the composition are prepared at a predetermined temperature T1 (step S10).
[0013] In step S10, the Li compound is a material that serves as a Li raw material for LCPO. The Co compound is a material that serves as a Co raw material for LCPO. The P compound is a material that serves as a P raw material for LCPO. The powders of the Li compound, Co compound and P compound are weighed and prepared so that the material obtained by firing in step S13 described below has a composition of LCPO, i.e., Li2CoP2O7. The temperature T1 at which the powders of the Li compound, Co compound and P compound are prepared is a temperature below 40°C, for example, room temperature.
[0014] The powders of the Li compound, the Co compound, and the P compound prepared at the temperature T1 are mixed while water is added at the temperature T1 (step S11). In step S11, the amount of water added is set to a certain ratio to the total weight of the powders of the Li compound, Co compound, and P compound, for example, the total weight of water to be contained in the mixed material of the Li compound, Co compound, and P compound by the addition is set to 2.0% by weight to 38.3% by weight of the total weight of the powders before the addition. Note that pure water can be used as the water added to the powders of the Li compound, Co compound, and P compound. The water to be added does not need to contain other substances such as citric acid.
[0015] In step S11, water is gradually added to the powders of the Li compound, Co compound, and P compound to be mixed. For example, a method is used in which water is added little by little while mixing the powders of the Li compound, Co compound, and P compound. Alternatively, a method may be used in which mixing of the powders of the Li compound, Co compound, and P compound and adding of a small amount of water are alternately repeated. For example, the water may be added by dripping or spraying the powders of the Li compound, Co compound, and P compound to be mixed. After the addition of water, further mixing may be performed at a temperature T1. For example, the material obtained in step S11 is in a powder form.
[0016] The material obtained by adding water to and mixing the powders of Li compound, Co compound, and P compound at a temperature T1 (step S11) is heated to a temperature T2 higher than the temperature T1, and further mixed at the temperature T2 (step S12). In step S12, the temperature T2 is set, for example, in the range of 40° C. to 60° C. For example, the material obtained in step S12 is in a powder form.
[0017] By the above steps S11 and S12, a material containing a precursor for LCPO, for example, a material containing lithium phosphate (Li3PO4) and ammonium cobalt phosphate (NH4CoPO4) as described below, is produced.
[0018] The material obtained by adding water and mixing at temperature T1 (step S11) and mixing at a higher temperature T2 (step S12), i.e., a material containing an LCPO precursor, is fired at a temperature T3 higher than temperature T2 (step S13). In step S13, temperature T3 is set to, for example, in the range of 650°C to 690°C.
[0019] By performing firing at such a temperature T3 (step S13), an LCPO is obtained (step S14). 1, the Li, Co, and P raw materials are reacted in the presence of water by mixing at temperature T1 (step S11) and then heating and mixing at a higher temperature T2 (step S12). This results in the formation of an LCPO precursor with excellent uniformity in the distribution of the Li, Co, and P components. The formation of such an LCPO precursor with excellent uniformity of each component makes it possible to obtain an LCPO with suppressed generation of heterogeneous phases by calcination (step S13).
[0020] The above-mentioned method for producing LCPO will now be described in more detail. FIG. 2 is a diagram showing an example of a method for producing lithium cobalt pyrophosphate according to the first embodiment.
[0021] First, powders of Li raw material, Co raw material and P raw material are prepared at a temperature T1 in amounts based on the composition of LCPO (step S20). For example, lithium carbonate (Li2CO3) is used as the Li raw material powder. For example, cobalt carbonate (CoCO3) or basic cobalt carbonate (xCoCO3·yCo(OH)2·zH2O) is used as the Co raw material powder. For example, ammonium dihydrogen phosphate (NH4H2PO4) is used as the P raw material powder. These Li2CO3, CoCO3 and NH4H2PO4 powders are weighed and prepared so as to have the composition of LCPO obtained by firing in step S25 described later, that is, Li2CoP2O7. For example, 150.5 g of Li2CO3 powder, 250.3 g of basic CoCO3 powder and 469.5 g of NH4H2PO4 powder are weighed and prepared. The temperature T1 at which these powders are prepared is below 40° C., for example room temperature.
[0022] The prepared powders of Li2CO3, basic CoCO3, and NH4H2PO4 are mixed at a temperature T1 (step S21). For example, the powders of Li2CO3, basic CoCO3, and NH4H2PO4 are mixed at a temperature T1 for 10 minutes. Note that this step S21 in which the powders of Li2CO3, basic CoCO3, and NH4H2PO4 are mixed at a temperature T1 can also be considered as one form of preparation of the powders of the Li raw material, the Co raw material, and the P raw material at a temperature T1.
[0023] The powders of Li2CO3, basic CoCO3 and NH4H2PO4 mixed (or prepared) at temperature T1 (step S21) are mixed while adding a certain amount of water (H2O) at temperature T1 (step S22). The amount of water added is set, for example, so that the total weight of water to be contained in the mixed material of Li2CO3, basic CoCO3 and NH4H2PO4 by the addition is 2.0% by weight to 38.3% by weight of the total weight of the powders before the addition. As an example, 17cc to 180cc of water is added. For example, a method is used in which 125cc of water is added over 15 minutes while mixing the powders of Li2CO3, basic CoCO3 and NH4H2PO4 at temperature T1. In step S22, the material obtained by adding and mixing a certain amount of water at temperature T1 may be further mixed at temperature T1 after the addition of the certain amount of water. For example, after the addition of the certain amount of water, further mixing is performed at temperature T1 for 15 minutes. For example, the material obtained in step S22 is in powder form. This step S22 produces a precursor for LCPO, mainly Li3PO4.
[0024] In the LCPO production method shown in FIG. 2, a material containing Li3PO4, which is a precursor for LCPO, is formed by the steps up to step S22. A material obtained by adding a certain amount of water to and mixing the powders of Li2CO3, basic CoCO3, and NH4H2PO4 at a temperature T1 (step S22), i.e., a material containing a precursor for LCPO (mainly Li3PO4), is heated to a temperature T2 higher than the temperature T1, and further mixed at the temperature T2 (step S23). The temperature T2 is set, for example, in the range of 40°C to 60°C. For example, the material obtained by adding a certain amount of water to and mixing at the temperature T1 is heated to a temperature T2=50°C, and further mixed at the temperature T2 for 15 minutes. For example, the material obtained in step S23 is in a powder form. By this step S23, a precursor for LCPO, mainly NH4CoPO4, is produced.
[0025] In the LCPO production method shown in FIG. 2, a material containing Li3PO4 and NH4CoPO4, which are precursors for LCPO, is formed by the steps up to step S23. The material obtained by mixing at temperature T2 (step S23), i.e., the material containing LCPO precursors Li3PO4 and NH4CoPO4, is dried at temperature T4 higher than temperature T2 (step S24). Temperature T4 is set to, for example, 90°C. For example, the material obtained by mixing at temperature T2 is heated to temperature T4=90°C, and drying is terminated when the temperature reaches 90°C. By such drying, the moisture in the material is evaporated and removed.
[0026] The material obtained by drying (step S24) is placed in a heat-resistant container such as a sagger, and is fired at a temperature T3 higher than the temperature T4 (and the temperature T2) (step S25). The temperature T3 is set, for example, in the range of 650°C to 690°C. The firing is performed in an air atmosphere or a non-oxidizing atmosphere. For example, the material obtained by drying is fired in an air atmosphere at 680°C for 10 hours. The material obtained by drying is crystallized by firing, thereby obtaining LCPO. In this example, 500g of LCPO is obtained from the raw materials of 150.5g of Li2CO3, 250.3g of basic CoCO3, and 469.5g of NH4H2PO4.
[0027] 2, a Li raw material, a Co raw material, and a P raw material are mixed at a temperature T1 (step S21), and then mixed at temperature T1 in the presence of water (step S22), and heated and mixed at a higher temperature T2 (step S23), to react the Li raw material, the Co raw material, and the P raw material. This forms an LCPO precursor with excellent uniformity in the distribution of the Li, Co, and P components.
[0028] For example, when the above-mentioned Li2CO3, CoCO3 and NH4H2PO4 are used as the Li source, Co source and P source, respectively, the reaction shown in the following formula (1) proceeds in the LCPO production method shown in FIG.
[0029] Li2CO3+CoCO3+2NH4H2PO4→2 / 3Li3PO4+NH4CoPO4+1 / 3NH4H2PO4+2CO2+2 / 3NH3+2H2O...(1) Here, the water-soluble P raw material NH4H2PO4 dissolves in water, and the dissolved NH4H2PO4 reacts with the Li raw material Li2CO3 and the Co raw material CoCO3 as shown in formula (1), to generate LCPO precursors Li3PO4 and NH4CoPO4. In the LCPO production method shown in Fig. 2, in step S22, Li3PO4 is mainly generated in the Li raw material Li2CO3, Co raw material CoCO3, and P raw material NH4H2PO4 are mixed at temperature T1 while a certain amount of water is added, and in step S23, NH4CoPO4 is mainly generated in the mixing at a higher temperature T2. Note that carbon dioxide (CO2) gas is generated, for example, in steps S22 and S23, and ammonia (NH3) gas is generated, for example, in steps S23 to S25.
[0030] The Li3PO4 and NH4CoPO4 produced by the reaction of formula (1) that proceeds with mixing and heating (steps S22 and S23) of the Li raw material Li2CO3 and the Co raw material CoCO3 in the presence of a certain amount of water are uniformly dispersed in the material and mixed at the atomic level. The P raw material NH4H2PO4 remains unreacted with the Li raw material Li2CO3 and the Co raw material CoCO3, but since it is dissolved in water once, NH4H2PO4 is also uniformly dispersed in the material as it is mixed. As a result, Li3PO4, NH4CoPO4, and NH4H2PO4 are well mixed and dispersed, and an LCPO precursor with excellent uniformity in the distribution of the Li component, Co component, and P component is formed.
[0031] In the LCPO production method shown in FIG. 2, an LCPO precursor having excellent uniformity in the distribution of the Li, Co, and P components is formed, and an LCPO in which the generation of heterogeneous phases is suppressed can be obtained by drying at a temperature T4 (step S24) and then firing at a higher temperature T3 (step S25).
[0032] 2, the amount of water added in step S22 is set so that the total weight of water contained in the mixed powder of the Li, Co, and P raw materials by the addition is 2.0% by weight to 38.3% by weight, preferably 26.6% by weight, of the total weight of the powder before the addition. If the amount of water is less than 2.0% by weight, the dissolution of the P raw material is likely to be insufficient, and if the amount of water exceeds 38.3% by weight, the drying time in step S24 becomes longer and lumps are likely to occur.
[0033] In the LCPO production method shown in Fig. 2, the temperature T2 during mixing in step S23 is set to 40°C to 60°C, preferably 50°C. If the temperature T2 is lower than 40°C, it becomes difficult to produce NH4CoPO4 sufficiently, and if the temperature T2 is higher than 60°C, water will evaporate too much, making the reaction prone to unevenness.
[0034] 2, the temperature T3 during firing in step S25 is set to 650° C. to 690° C., preferably 680° C. If the temperature T3 is below 650° C., phases other than LCPO are likely to occur, while if the temperature T3 exceeds 690° C., the material being fired will melt, making it likely that phases other than LCPO will occur.
[0035] Phases other than LCPO tend to be easily formed when the distribution of the Li, Co, and P components contained in the LCPO precursor before calcination is non-uniform. That is, when an LCPO precursor in which the distribution of the Li, Co, and P components is non-uniform is calcined, phases tend to be easily formed. Even if the Li, Co, and P raw materials are mixed for a long time or pulverized in order to increase the uniformity of the distribution of each component, it may be difficult to obtain an LCPO in which the formation of phases is suppressed. Furthermore, the time and cost required to obtain an LCPO in which the formation of phases is suppressed may increase.
[0036] In contrast, the LCPO production process shown in FIG. 2 makes it possible to form an LCPO precursor having excellent uniformity in the distribution of the Li, Co, and P components in a relatively short time and at reduced cost, and then calcining the precursor to obtain an LCPO in which the formation of other phases is suppressed.
[0037] [Second embodiment] FIG. 3 is a diagram illustrating a method for producing lithium cobalt pyrophosphate according to the second embodiment.
[0038] In the method for producing LCPO shown in FIG. 3, first, powders of a Li compound, a Co compound and a P compound in amounts based on the composition are prepared at a predetermined temperature T1 (step S30). In step S30, the Li compound is a material that serves as a Li raw material for LCPO. The Co compound is a material that serves as a Co raw material for LCPO. The P compound is a material that serves as a P raw material for LCPO. Powders of the Li compound, Co compound, and P compound are weighed and prepared so as to obtain an LCPO having a composition of Li2CoP2O7, i.e., Li2CoP2O7, which is obtained by firing in step S32 described later. The temperature T1 at which the powders of the Li compound, Co compound, and P compound are prepared is a temperature less than 40°C, for example, room temperature.
[0039] Powders of a Li compound, a Co compound, and a P compound prepared at a temperature T1 are heated to a temperature T2 higher than the temperature T1, and mixed with water at the temperature T2 (step S31).
[0040] In step S31, the temperature T2 is set to a range of 40°C to 60°C, for example. In step S31, the amount of water to be added is set to a certain ratio with respect to the total weight of the powders of the Li compound, Co compound, and P compound. For example, the total weight of water to be contained in the mixed material of the Li compound, Co compound, and P compound by the addition is set to be 14.9% by weight to 95.8% by weight of the total weight of the powders before the addition. Note that pure water can be used as the water to be added to the powders of the Li compound, Co compound, and P compound. The water to be added does not need to contain other substances such as citric acid.
[0041] In step S31, water is gradually added to the powders of the Li compound, Co compound, and P compound to be mixed. For example, a method is used in which water is added little by little while mixing the powders of the Li compound, Co compound, and P compound. Alternatively, a method may be used in which mixing the powders of the Li compound, Co compound, and P compound and adding a small amount of water are alternately repeated. For example, water can be added by dripping or spraying water onto the powders of the Li compound, Co compound, and P compound to be mixed. For example, the material obtained in step S31 is in powder form.
[0042] In step S31, a material containing a precursor for LCPO, for example, a material containing Li3PO4 and NH4CoPO4, is produced. The material obtained by adding and mixing water at temperature T2 (step S31), i.e., the material containing the LCPO precursor, is fired at temperature T3 higher than temperature T2 (step S32). In step S32, temperature T3 is set to, for example, in the range of 650°C to 690°C.
[0043] By performing the calcination at such a temperature T3 (step S32), an LCPO is obtained (step S33). 3, the Li, Co, and P raw materials are reacted in the presence of water while being mixed (step S31) at a temperature T2 higher than temperature T1. This forms an LCPO precursor having excellent uniformity in the distribution of the Li, Co, and P components. The formation of such an LCPO precursor having excellent uniformity of each component makes it possible to obtain an LCPO in which the formation of different phases is suppressed by calcination (step S32).
[0044] The above-mentioned method for producing LCPO will now be described in more detail. FIG. 4 is a diagram showing an example of a method for producing lithium cobalt pyrophosphate according to the second embodiment.
[0045] First, powders of Li raw material, Co raw material and P raw material in amounts based on the composition of LCPO are prepared at temperature T1 (step S40). For example, Li2CO3 is used as the powder of Li raw material. For example, CoCO3 or basic CoCO3 is used as the powder of Co raw material. For example, NH4H2PO4 is used as the powder of P raw material. These powders of Li2CO3, CoCO3 and NH4H2PO4 are weighed and prepared so as to obtain the composition of LCPO obtained by firing in step S44 described later, that is, Li2CoP2O7. For example, 150.5 g of Li2CO3 powder, 250.3 g of basic CoCO3 powder and 469.5 g of NH4H2PO4 powder are weighed and prepared. The temperature T1 at which these powders are prepared is a temperature below 40°C, for example, room temperature.
[0046] The prepared powders of Li2CO3, basic CoCO3, and NH4H2PO4 are heated to a temperature T2 higher than the temperature T1 and mixed (step S41). The powders of Li2CO3, basic CoCO3, and NH4H2PO4 may be mixed during the process of heating to the temperature T2, or may be mixed after heating to the temperature T2.
[0047] Then, the powders of Li2CO3, basic CoCO3 and NH4H2PO4 heated to the temperature T2 are mixed while a certain amount of water (H2O) is added at the temperature T2 (step S42). The amount of water added is set, for example, so that the total weight of water contained in the mixed material of Li2CO3, basic CoCO3 and NH4H2PO4 by the addition is 14.9% by weight to 95.8% by weight of the total weight of the powders before the addition. As an example, 70cc to 450cc of water is added. For example, a method is used in which the powders of Li2CO3, basic CoCO3 and NH4H2PO4 are mixed for 15 minutes while spraying 300cc of water at the temperature T2. For example, the material obtained in step S42 is in a powder form. By this step S42, Li3PO4 and NH4CoPO4, which are precursors for LCPO, are both produced.
[0048] In the LCPO production method shown in FIG. 4, a material containing Li3PO4 and NH4CoPO4, which are LCPO precursors, is formed by the steps up to step S42. The material obtained by adding and mixing a certain amount of water at temperature T2 (step S42), i.e., a material containing LCPO precursors Li3PO4 and NH4CoPO4, is dried at a temperature T4 higher than temperature T2 (step S43). Temperature T4 is set to, for example, 90°C. For example, the material obtained by adding and mixing a certain amount of water at temperature T2 is heated to temperature T4=90°C, and drying is terminated when the temperature reaches 90°C. By such drying, the moisture in the material is evaporated and removed.
[0049] The material obtained by drying (step S43) is placed in a heat-resistant container such as a sagger, and is fired at a temperature T3 higher than the temperature T4 (and the temperature T2) (step S44). The temperature T3 is set, for example, in the range of 650°C to 690°C. The firing is performed, for example, in an air atmosphere or a non-oxidizing atmosphere. For example, the material obtained by drying is fired in an air atmosphere at 680°C for 10 hours. The material obtained by drying is crystallized by firing, thereby obtaining LCPO. In this example, 500g of LCPO is obtained from the raw materials of 150.5g of Li2CO3, 250.3g of basic CoCO3, and 469.5g of NH4H2PO4.
[0050] 4, a Li source, a Co source, and a P source are mixed and reacted in the presence of water at a temperature T2 higher than the temperature T1 (step S42), thereby forming an LCPO precursor having excellent uniformity in the distribution of the Li, Co, and P components.
[0051] For example, when the Li, Co, and P raw materials are Li2CO3, CoCO3, and NH4H2PO4, respectively, the reaction shown in formula (1) proceeds in the LCPO manufacturing method shown in Fig. 4. The water-soluble P raw material NH4H2PO4 dissolves in water, and the dissolved NH4H2PO4 reacts with the Li raw material Li2CO3 and the Co raw material CoCO3 as shown in formula (1), to generate LCPO precursors Li3PO4 and NH4CoPO4. In the LCPO manufacturing method shown in Fig. 4, in step S42, a certain amount of water is added to the Li raw material Li2CO3, the Co raw material CoCO3, and the P raw material NH4H2PO4, and mixed at temperature T2, to generate both Li3PO4 and NH4CoPO4. Incidentally, CO2 gas is generated, for example, in step S42, and NH3 gas is generated, for example, in steps S42 to S44.
[0052] The reaction of formula (1) that proceeds with the addition of a certain amount of water to the heated Li source Li2CO3 and Co source CoCO3 and mixing them (step S42) produces Li3PO4 and NH4CoPO4 that are uniformly dispersed in the material and mixed at the atomic level. The P source NH4H2PO4 is once dissolved in water, and is uniformly dispersed in the material as it is mixed, although some unreacted NH4H2PO4 remains. As a result, Li3PO4, NH4CoPO4, and NH4H2PO4 are well mixed and dispersed, forming an LCPO precursor with excellent uniformity in the distribution of the Li, Co, and P components.
[0053] In the LCPO production method shown in FIG. 4, an LCPO precursor having excellent uniformity in the distribution of the Li, Co, and P components is formed, and an LCPO in which the generation of heterogeneous phases is suppressed can be obtained by drying at a temperature T4 (step S43) and then firing at a higher temperature T3 (step S44).
[0054] 4, the amount of water added in step S42 is set so that the total weight of water contained in the mixed material of the Li raw material, the Co raw material, and the P raw material by the addition is 14.9% by weight to 95.8% by weight, preferably 63.9% by weight, of the total weight of the powder before the addition. If the amount of water is less than 14.9% by weight, the dissolution of the P raw material is likely to be insufficient, and if the amount of water exceeds 95.8% by weight, the drying time in step S43 becomes longer and lumps are likely to occur.
[0055] In the production of LCPO shown in Fig. 4, the temperature T2 during mixing in step S42 is set to 40°C to 60°C, preferably 50°C. If the temperature T2 is below 40°C, it becomes difficult to produce NH4CoPO4 sufficiently, and if the temperature T2 is above 60°C, water will evaporate too much, making the reaction prone to unevenness.
[0056] 4, the temperature T3 during firing in step S44 is set to 650° C. to 690° C., preferably 680° C. If the temperature T3 is below 650° C., phases other than LCPO are likely to occur, while if the temperature T3 exceeds 690° C., the material being fired will melt, making it likely that phases other than LCPO will occur.
[0057] According to the LCPO production method shown in FIG. 4, an LCPO precursor having excellent distribution uniformity of the Li, Co, and P components can be formed in a relatively short time and at reduced cost, and an LCPO in which the formation of other phases is suppressed can be obtained by firing the precursor.
[0058] In the above, in the first and second embodiments, a method for producing LCPO capable of suppressing the formation of different phases has been described. In the above explanation, an example was given in which Li2CO3 was used as the Li raw material, CoCO3 or basic CoCO3 was used as the Co raw material, and NH4H2PO4 was used as the P raw material, but other materials can be used for the Li raw material, Co raw material, and P raw material. For example, lithium nitrate (LiNO3), lithium hydroxide (LiOH), etc. can be used for the Li raw material. Cobalt nitrate (Co(NO3)2 or Co(NO3)2·6H2O), cobalt hydroxide (Co(OH)2), cobalt oxide (CoO, Co3O4), etc. can be used for the Co raw material. Ammonium monohydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), etc. can be used for the P raw material.
[0059] The combination of Li2CO3 and CoCO3 as shown in the above example is advantageous in that it is easy to suppress side reactions (oxidation of the Co raw material by oxygen in the air). Also, (NH4)2HPO4 generates more NH3 gas than NH4H2PO4, and H3PO4 accelerates the dissolution reaction of the Li raw material and the Co raw material, which may cause aggregation or solidification depending on the conditions. From these points of view, it is advantageous to use NH4H2PO4 as shown in the above example.
[0060] Meanwhile, in the field of batteries, LCPO is being considered for use as a positive electrode active material. As one type of battery, a solid-state battery is known that includes a positive electrode layer containing a positive electrode active material and a solid electrolyte, etc., a negative electrode layer containing a negative electrode active material and a solid electrolyte, etc., and a layer of a solid electrolyte provided between the positive electrode layer and the negative electrode layer. Since a solid-state battery does not use a flammable organic electrolyte solution as in a lithium-ion secondary battery, it has the advantages of being able to reduce the risks of leakage, combustion, explosion, and generation of toxic gases and to increase safety, being easy to handle in the atmosphere, and being able to maintain performance even under low and high temperature conditions.
[0061] LCPO is used, for example, as a positive electrode active material contained in the positive electrode layer of such solid-state batteries. Because LCPO operates at a relatively high voltage when it functions as a positive electrode, it is one of the effective materials for realizing a battery cell with a high operating voltage by widening the difference with the voltage when the active material in the negative electrode layer operates as a negative electrode.
[0062] An example of a solid-state battery using LCPO as a positive electrode active material will be described below as the third embodiment. [Third embodiment] Fig. 5 is a diagram showing an example of a configuration of a solid-state battery. Fig. 5(A) is a schematic perspective view of an exterior of an example of a solid-state battery. Fig. 5(B) is a schematic cross-sectional view of a main part of an example of a solid-state battery. Fig. 5(B) is an example of a cross section taken along plane P1 of Fig. 5(A).
[0063] The solid-state battery 1A shown in Figures 5(A) and 5(B) is an example of a chip-type battery. The solid-state battery 1A has a solid-state battery body 1Aa and a current collector 40 (electrode) and a current collector 50 (electrode) provided at both ends of the solid-state battery body 1Aa, respectively.
[0064] As shown in FIG. 5B, the solid-state battery body 1Aa has a structure in which an electrolyte layer 30, a positive electrode layer 10, and a negative electrode layer 20 are laminated. One electrolyte layer 30 is interposed between one pair of the positive electrode layer 10 and the negative electrode layer 20, and one electrolyte layer 30 is provided on the top positive electrode layer 10 and below the bottom negative electrode layer 20. The positive electrode layer 10 is connected to a current collector 40 provided at one end of the solid-state battery body 1Aa, and the negative electrode layer 20 is connected to a current collector 50 provided at the other end of the solid-state battery body 1Aa. The side of the positive electrode layer 10 is surrounded by, for example, an electrolyte layer 30 provided in the same layer as the positive electrode layer 10, except for the connection portion with the current collector 40, and the side of the negative electrode layer 20 is surrounded by, for example, an electrolyte layer 30 provided in the same layer as the negative electrode layer 20, except for the connection portion with the current collector 50. As shown in FIGS. 5(A) and 5(B), for example, a group of stacked electrolyte layers 30 (their oxide solid electrolytes) are exposed on the outer surface of the solid-state battery body 1Aa.
[0065] On the outermost electrolyte layer 30 of the solid battery body 1Aa, as shown in FIGS. 5(A) and 5(B), a polarity marker 2 is provided to indicate which of the current collectors 40 and 50 is on the positive electrode side and which is on the negative electrode side. In this example, a polarity marker 2 is provided to indicate that the current collector 50 connected to the negative electrode layer 20 is on the negative electrode side.
[0066] The electrolyte layer 30 of the solid battery body 1Aa contains a solid electrolyte material. An oxide solid electrolyte is used as the solid electrolyte material of the electrolyte layer 30. For example, LAGP, which is a type of oxide solid electrolyte of the NASICON (Na super ionic conductor) type (also referred to as the "NASICON type"), is used in the electrolyte layer 30. LAGP is an oxide solid electrolyte represented by the general formula Li 1+s Al s Ge 2-s (PO4)3 (0 < s ≦ 1), and is also referred to as aluminum-substituted lithium germanium phosphate gel, etc. In this example, as the LAGP of the electrolyte layer 30, Li 1.5 Al 0.5 Ge 1.5 (PO4)3 with a composition ratio s = 0.5 is used.
[0067] The positive electrode layer 10 of the solid battery body 1Aa contains a solid electrolyte material, a conductive auxiliary agent, and a positive electrode active material. An oxide solid electrolyte is used as the solid electrolyte material of the positive electrode layer 10. For example, the same type of material as the oxide solid electrolyte used in the electrolyte layer 30 is used as the oxide solid electrolyte of the positive electrode layer 10. That is, in this example, LAGP is used as the oxide solid electrolyte of the positive electrode layer 10. As the conductive auxiliary agent of the positive electrode layer 10, for example, carbon materials such as carbon fiber, carbon black, graphite, graphene, and carbon nanotubes are used. In addition, as the conductive auxiliary agent, a metal material, a metal silicide material such as nickel silicide or iron silicide, a conductive polymer material, etc. may be used. The positive electrode active material of the positive electrode layer 10 uses LCPO obtained by the manufacturing method described in the first or second embodiment above. The voltage of LCPO when operating as a positive electrode is 5V (Li / Li +) To such an extent. In addition to LCPO, the cathode active material of the cathode layer 10 may contain other cathode active materials, such as lithium cobalt phosphate (LiCoPO4), lithium vanadium phosphate (Li3V2(PO4)3, hereinafter referred to as "LVP"), etc.
[0068] The negative electrode layer 20 of the solid battery body 1Aa contains a solid electrolyte material, a conductive auxiliary agent, and a negative electrode active material. An oxide solid electrolyte is used as the solid electrolyte material of the negative electrode layer 20. As the oxide solid electrolyte of the negative electrode layer 20, for example, the same kind of material as the oxide solid electrolyte used in the electrolyte layer 30 is used. That is, in this example, LAGP is used as the oxide solid electrolyte of the negative electrode layer 20. As the conductive auxiliary agent of the negative electrode layer 20, for example, carbon materials such as carbon fiber, carbon black, graphite, graphene, and carbon nanotubes are used. In addition, as the conductive auxiliary agent, a metal material, a metal silicide material such as nickel silicide and iron silicide, a conductive polymer material, etc. may be used. The negative electrode active material of the negative electrode layer 20 includes LVP, lithium titanate (Li4Ti5O 12 ), titanium oxide (TiO2), niobium oxide (Nb2O5), etc. In addition, the negative electrode active material of the negative electrode layer 20 includes NASICON-type LATP (general formula Li 1+t Al t Ti 2-t (PO4)3, 0 < t ≦ 1), and metal silicide materials such as nickel silicide and iron silicide may be used. In the negative electrode layer 20, one kind of material may be used as the negative electrode active material, or two or more kinds of materials may be used.
[0069] During charging of the solid battery 1A, lithium ions are conducted and taken into the negative electrode layer 20 from the cathode layer 10 through the electrolyte layer 30, and during discharging, lithium ions are conducted and taken into the cathode layer 10 from the negative electrode layer 20 through the electrolyte layer 30. In the solid battery 1A, such lithium ion conduction realizes the charge and discharge operation.
[0070] A method for manufacturing the solid battery 1A having the configuration shown in FIGS. 5(A) and 5(B) will be described below. (LAGP powder) First, the raw materials for LAGP, Li2CO3, aluminum oxide (Al2O3), germanium oxide (GeO2), and NH4H2PO4 powders, are weighed out and mixed to a specified composition ratio. The mixture obtained by mixing is pre-fired at a temperature of 300°C to 400°C for 3 to 5 hours. The powder obtained by pre-fire is melted by heat treatment at a temperature of 1200°C to 1400°C for 1 to 2 hours. The material obtained by melting is rapidly cooled and vitrified. This results in amorphous LAGP powder.
[0071] The obtained LAGP powder is pulverized and adjusted to a desired particle size p (median diameter D50). Here, the particle size p of the LAGP powder for the electrolyte layer is adjusted to, for example, 2 μm≦p≦5 μm. In addition, the particle size p of the LAGP powder for the positive electrode layer and the negative electrode layer (each also referred to as "electrode layer") is adjusted to be smaller than that for the electrolyte layer, for example, 0.2 μm≦p≦1.0 μm, from the viewpoint of ensuring the lithium ion conductivity of the electrode layer by interposing the LAGP powder between the particles of the powdered active material.
[0072] For example, by such a method, LAGP powders to be used for the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20 of a solid-state battery 1A as shown in FIG. 5(B) are prepared. (electrolyte layer) As an example, the LAGP powder having a particle size p for the electrolyte layer obtained by the above method is mixed with an organic binder, a solvent, etc., and is applied to a carrier such as a polyethylene terephthalate (PET) film by a doctor blade method, etc., to form a plastic electrolyte layer green sheet (also called an "LAGP green sheet"). For example, the electrolyte layer green sheet thus formed is used to form an electrolyte layer 30 as shown in FIG. 5(B).
[0073] As another example, the LAGP powder having a particle size p for the electrolyte layer obtained by the above method is molded into a green compact by a uniaxial hydraulic press and sintered at a temperature of 900° C. for 3 hours. This forms a substrate for the electrolyte layer (also called a “LAGP substrate”). For example, the substrate for the electrolyte layer formed in this manner is used to form an electrolyte layer 30 as shown in FIG. 5(B).
[0074] (Positive and negative electrode layers) As an example, the LAGP powder having a particle size p for the electrode layer obtained by the above method, the conductive assistant, the positive electrode active material containing at least LCPO, the binder such as acrylic resin, the solvent, etc. are mixed and coated on a carrier such as a PET film by a doctor blade method, etc. to form a green sheet for the positive electrode layer. The LAGP powder having a particle size p for the electrode layer obtained by the above method, the conductive assistant, the negative electrode active material, the binder such as acrylic resin, the solvent, etc. are mixed and coated on a carrier such as a PET film by a doctor blade method, etc. to form a green sheet for the negative electrode layer. For example, the green sheet for the positive electrode layer and the green sheet for the negative electrode layer thus formed are used to form the positive electrode layer 10 and the negative electrode layer 20, respectively, as shown in FIG. 5(B).
[0075] As another example, the LAGP powder having a particle size p for the electrode layer obtained by the above method, a conductive assistant, a positive electrode active material containing at least LCPO, a binder such as acrylic resin, a solvent, etc. are mixed to form a paste for the positive electrode layer. The LAGP powder having a particle size p for the electrode layer obtained by the above method, a conductive assistant, a negative electrode active material, a binder such as acrylic resin, a solvent, etc. are mixed to form a paste for the negative electrode layer. For example, the paste for the positive electrode layer and the paste for the negative electrode layer thus formed are used to form the positive electrode layer 10 and the negative electrode layer 20, respectively, as shown in FIG. 5(B).
[0076] (Solid-state battery body) For example, the solid-state battery body 1Aa shown in FIG. 5(B) is formed by a green sheet lamination method (first formation example shown in FIG. 6 and FIG. 7) using the above-mentioned electrolyte layer green sheet, positive electrode layer green sheet, and negative electrode layer green sheet. Alternatively, the solid-state battery body 1Aa shown in FIG. 5(B) is formed by a screen printing method (second formation example shown in FIG. 8 and FIG. 9) using the above-mentioned electrolyte layer substrate, positive electrode layer paste, and negative electrode layer paste. Alternatively, the solid-state battery body 1Aa shown in FIG. 5(B) is formed by a screen printing method (third formation example shown in FIG. 10 and FIG. 11) using the above-mentioned electrolyte layer green sheet, positive electrode layer paste, and negative electrode layer paste.
[0077] Fig. 6 and Fig. 7 are diagrams for explaining a first forming example of a solid-state battery body. Fig. 6(A) to Fig. 6(C) each show a schematic perspective view of a main part of layers included in the solid-state battery body. Fig. 7 shows a schematic cross-sectional view of a main part of a lamination process of layers included in the solid-state battery body.
[0078] An electrolyte layer green sheet 31 (LAGP green sheet) having a shape as shown in Fig. 6(A) is used for the electrolyte layers 30 provided above and below the positive electrode layer 10 and the electrolyte layers 30 provided above and below the negative electrode layer 20 of the solid-state battery body 1Aa as shown in Fig. 5(B). The electrolyte layer green sheet 31 is prepared as it is or by cutting the one obtained by the above method.
[0079] For the positive electrode layer 10 of the solid-state battery body 1Aa as shown in FIG. 5(B), a positive electrode layer green sheet 11 having a shape as shown in FIG. 6(B) (middle view) is used. The positive electrode layer green sheet 11 is prepared as it is or after cutting the one obtained by the above method. Furthermore, as the electrolyte layer 30 provided in the same layer as the positive electrode layer 10 of the solid-state battery body 1Aa, an electrolyte layer green sheet 31 having a shape as shown in FIG. 6(B) (upper view), that is, a shape capable of surrounding the positive electrode layer green sheet 11 except for one end, is prepared. The electrolyte layer green sheet 31 is prepared by cutting the one obtained by the above method. The prepared positive electrode layer green sheet 11 and electrolyte layer green sheet 31 may be combined in advance so that the positive electrode layer green sheet 11 is surrounded by the electrolyte layer green sheet 31 except for one end, as shown in FIG. 6(B) (lower view).
[0080] For the negative electrode layer 20 of the solid-state battery body 1Aa as shown in FIG. 5(B), a negative electrode layer green sheet 21 having a shape as shown in FIG. 6(C) (middle view) is used. The negative electrode layer green sheet 21 is prepared as it is or after cutting the one obtained by the above method. Furthermore, as the electrolyte layer 30 provided in the same layer as the negative electrode layer 20 of the solid-state battery body 1Aa, an electrolyte layer green sheet 31 having a shape as shown in FIG. 6(C) (upper view), that is, a shape capable of surrounding the negative electrode layer green sheet 21 except for one end, is prepared. The electrolyte layer green sheet 31 is prepared by cutting the one obtained by the above method. The prepared negative electrode layer green sheet 21 and electrolyte layer green sheet 31 may be combined in advance so that the negative electrode layer green sheet 21 is surrounded by the electrolyte layer green sheet 31 except for one end, as shown in FIG. 6(C) (lower view).
[0081] The electrolyte layer green sheet 31, the positive electrode layer green sheet 11, and the negative electrode layer green sheet 21 obtained as described above are laminated in the order shown in Fig. 7 and are thermally pressed together. This forms the basic structure (laminate) of the solid-state battery body 1Aa. A polarity marker 2 is provided on the uppermost electrolyte layer green sheet 31.
[0082] For convenience, Fig. 6(B) illustrates a state in which the positive electrode layer green sheet 11 is surrounded by the electrolyte layer green sheet 31 except for one end thereof, but by cutting at a predetermined position after lamination and thermocompression bonding according to the example of Fig. 7, a state in which the positive electrode layer green sheet 11 is surrounded by the electrolyte layer green sheet 31 except for one end thereof may be obtained. Similarly, Fig. 6(C) illustrates a state in which the negative electrode layer green sheet 21 is surrounded by the electrolyte layer green sheet 31 except for one end thereof, but by cutting at a predetermined position after lamination and thermocompression bonding according to the example of Fig. 7, a state in which the negative electrode layer green sheet 21 is surrounded by the electrolyte layer green sheet 31 except for one end thereof may be obtained.
[0083] 8 and 9 are diagrams for explaining a second example of forming a solid-state battery body. Fig. 8(A) to Fig. 8(D) each show a perspective view of a main part in a forming process of layers included in the solid-state battery body. Fig. 9 shows a cross-sectional view of a main part in a stacking process of layers included in the solid-state battery body.
[0084] An electrolyte layer substrate 32 (LAGP substrate) having a shape as shown in FIG. 8(A) is prepared by the above-mentioned powder compaction and sintering. A positive electrode layer paste 12 is applied by screen printing to a part of one surface of the electrolyte layer substrate 32 as shown in FIG. 8(B). After application, drying is performed to remove the solvent in the positive electrode layer paste 12. An insulating paste, for example, an electrolyte layer paste 33 containing an oxide solid electrolyte LAGP is applied by screen printing to the remaining part of one surface of the electrolyte layer substrate 32 as shown in FIG. 8(C). After application, drying is performed to remove the solvent in the electrolyte layer paste 33.
[0085] The positive electrode layer paste 12 and the electrolyte layer paste 33 may be applied by screen printing multiple times. In this case, drying for removing the solvent may be performed after each or both of the screen printing of the positive electrode layer paste 12 and the electrolyte layer paste 33, or may be performed all at once after the screen printing of the positive electrode layer paste 12 and the electrolyte layer paste 33 multiple times.
[0086] 8(A) to 8(C), as shown in Fig. 8(D), the negative electrode layer paste 22 is applied by screen printing to a portion of the other surface of the electrolyte layer substrate 32, and an insulating paste, for example, the electrolyte layer paste 33 is applied by screen printing to the remaining portion of the surface. After the application of the negative electrode layer paste 22 and the electrolyte layer paste 33, drying is performed to remove the solvent in the negative electrode layer paste 22 and the electrolyte layer paste 33.
[0087] The application of the negative electrode layer paste 22 and the electrolyte layer paste 33 by screen printing may be performed multiple times. In this case, drying for removing the solvent may be performed after each or both of the screen printing of the negative electrode layer paste 22 and the electrolyte layer paste 33, or may be performed all at once after the screen printing of the negative electrode layer paste 22 and the electrolyte layer paste 33 multiple times.
[0088] The laminate 3 as shown in Fig. 8(D) is laminated alternately with the electrolyte layer substrate 32 or the electrolyte layer green sheet 31 as shown in Fig. 9, and is thermocompression bonded. In this way, the basic structure (laminate) of the solid-state battery body 1Aa is formed. A polarity marker 2 is provided to the uppermost electrolyte layer substrate 32 or electrolyte layer green sheet 31.
[0089] 8(B) and 8(C) illustrate a state in which the side of the positive electrode layer paste 12 is exposed from one side of the electrolyte layer substrate 32 and the electrolyte layer paste 33 for convenience, but after lamination and thermocompression bonding according to the example of FIG. 9, cutting may be performed at a predetermined position to obtain a state in which the side of the positive electrode layer paste 12 is exposed from one side of the electrolyte layer substrate 32 and the electrolyte layer paste 33. Similarly, FIG. 8(D) illustrates a state in which the side of the negative electrode layer paste 22 is exposed from one side of the electrolyte layer substrate 32 and the electrolyte layer paste 33 for convenience, but after lamination and thermocompression bonding according to the example of FIG. 9, cutting may be performed at a predetermined position to obtain a state in which the side of the negative electrode layer paste 22 is exposed from one side of the electrolyte layer substrate 32 and the electrolyte layer paste 33.
[0090] Fig. 10 and Fig. 11 are diagrams for explaining a third example of forming a solid-state battery body. Fig. 10(A) to Fig. 10(E) each show a perspective view of a main part in a forming process of a layer included in a solid-state battery body. Fig. 11 shows a cross-sectional view of a main part in a stacking process of layers included in a solid-state battery body.
[0091] An electrolyte layer green sheet 31 having a shape as shown in Fig. 10(A) is prepared. A positive electrode layer paste 12 is applied to a portion of the electrolyte layer green sheet 31 by screen printing as shown in Fig. 10(B). After application, drying is performed to remove the solvent in the positive electrode layer paste 12. An insulating paste, for example, an electrolyte layer paste 33 is applied to the remaining portion of the electrolyte layer green sheet 31 by screen printing as shown in Fig. 10(C). After application, drying is performed to remove the solvent in the electrolyte layer paste 33.
[0092] The positive electrode layer paste 12 and the electrolyte layer paste 33 may be applied by screen printing multiple times. In this case, drying for removing the solvent may be performed after each or both of the screen printing of the positive electrode layer paste 12 and the electrolyte layer paste 33, or may be performed all at once after the screen printing of the positive electrode layer paste 12 and the electrolyte layer paste 33 multiple times.
[0093] Similarly, an electrolyte layer green sheet 31 having a shape as shown in Fig. 10(A) is prepared, and a negative electrode layer paste 22 is applied to a portion of the electrolyte layer green sheet 31 by screen printing as shown in Fig. 10(D). After application, drying is performed to remove the solvent in the negative electrode layer paste 22. An insulating paste, for example, an electrolyte layer paste 33 is applied to the remaining portion of the electrolyte layer green sheet 31 by screen printing as shown in Fig. 10(E). After application, drying is performed to remove the solvent in the electrolyte layer paste 33.
[0094] The application of the negative electrode layer paste 22 and the electrolyte layer paste 33 by screen printing may be performed multiple times. In this case, drying for removing the solvent may be performed after each or both of the screen printing of the negative electrode layer paste 22 and the electrolyte layer paste 33, or may be performed all at once after the screen printing of the negative electrode layer paste 22 and the electrolyte layer paste 33 multiple times.
[0095] A laminate 4 as shown in Fig. 10(C) and a laminate 5 as shown in Fig. 10(E) are alternately laminated and thermocompressed with an electrolyte layer green sheet 31 provided on the uppermost layer as shown in Fig. 11. This forms the basic structure (laminate) of the solid-state battery body 1Aa. A polarity marker 2 is provided on the electrolyte layer green sheet 31 of the uppermost layer.
[0096] 10(B) and 10(C) illustrate a state in which the side of the positive electrode layer paste 12 is exposed from one side of the electrolyte layer green sheet 31 and the electrolyte layer paste 33 for convenience, but after lamination and thermocompression bonding according to the example of FIG. 11, cutting may be performed at a predetermined position to obtain a state in which the side of the positive electrode layer paste 12 is exposed from one side of the electrolyte layer green sheet 31 and the electrolyte layer paste 33. Similarly, FIG. 10(D) and 10(E) illustrate a state in which the side of the negative electrode layer paste 22 is exposed from one side of the electrolyte layer green sheet 31 and the electrolyte layer paste 33 for convenience, but after lamination and thermocompression bonding according to the example of FIG. 11, cutting may be performed at a predetermined position to obtain a state in which the side of the negative electrode layer paste 22 is exposed from one side of the electrolyte layer green sheet 31 and the electrolyte layer paste 33.
[0097] (Firing) Fig. 12 is a diagram for explaining the firing of the basic structure of the solid-state battery body. Fig. 12(A) shows a schematic cross-sectional view of the main part of the basic structure of the solid-state battery body. Fig. 12(B) shows a schematic cross-sectional view of the main part of the firing process of the basic structure of the solid-state battery body.
[0098] A laminate 100, which is a basic structure of a solid-state battery body 1Aa, is obtained as shown in Fig. 12(A) by the method shown in Fig. 6 and Fig. 7, the method shown in Fig. 8 and Fig. 9, or the method shown in Fig. 10 and Fig. 11. The laminate 100 includes an electrolyte layer 30 before firing (corresponding to the above-mentioned electrolyte layer green sheet 31, electrolyte layer substrate 32, or electrolyte layer paste 33), a positive electrode layer 10 before firing (corresponding to the above-mentioned positive electrode layer green sheet 11 or positive electrode layer paste 12), and a negative electrode layer 20 before firing (corresponding to the above-mentioned negative electrode layer green sheet 21 or negative electrode layer paste 22).
[0099] The obtained laminate 100 is carried into a sintering furnace 120 as shown in Fig. 12(B). The carried-in laminate 100 is then sintered in the sintering furnace 120 in an air atmosphere to pyrolyze (degrease) the remaining binder, etc., and further sintered in a non-oxidizing atmosphere or an air atmosphere to sinter the LAGP. As a result, a solid-state battery body 1Aa having the sintered electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20 is formed.
[0100] (current collector) After the solid-state battery body 1Aa is formed, a current collector 40 is formed of silver (Ag) paste or the like at one end where the positive electrode layer 10 is exposed. Similarly, a current collector 50 is formed of Ag paste or the like at the other end of the solid-state battery body 1Aa where the negative electrode layer 20 is exposed. In addition to Ag paste, a conductive paste containing conductive particles such as various metal particles and carbon particles can also be used for the current collector 40 and the current collector 50. A conductive paste such as Ag paste is applied to both ends of the solid-state battery body 1Aa, and the conductive particles such as Ag in the conductive paste are sintered by firing to form the current collector 40 and the current collector 50. In this way, the current collector 40 connected to the positive electrode layer 10 is formed at one end of the solid-state battery body 1Aa, and the current collector 50 connected to the negative electrode layer 20 is formed at the other end of the solid-state battery body 1Aa, and a solid-state battery 1A having a configuration as shown in FIG. 5(A) and FIG. 5(B) is formed.
[0101] In the above-mentioned solid-state battery 1A, the positive electrode layer 10 of the solid-state battery body 1Aa uses, as a positive electrode active material, an LCPO obtained by the manufacturing method described in the above-mentioned first or second embodiment, i.e., an LCPO in which the generation of a different phase is suppressed. If the LCPO used as the positive electrode active material contains a different phase, it may result in a decrease in the operating voltage of the positive electrode, a decrease in the energy density, etc., and it may not be possible to obtain a solid-state battery that exhibits excellent charge / discharge characteristics. In contrast, in the above-mentioned solid-state battery 1A, an LCPO in which the generation of a different phase is suppressed is used as the positive electrode active material. This realizes a high-performance chip-type solid-state battery 1A with excellent charge / discharge characteristics.
[0102] Moreover, Fig. 13 is a diagram showing another example of the configuration of a solid-state battery. Fig. 13(A) is a schematic perspective view of a main part of an example of a solid-state battery. Fig. 13(B) is a schematic cross-sectional view of a main part of an example of a solid-state battery. Fig. 13(B) is an example of a cross section taken along plane P2 of Fig. 13(A).
[0103] The solid-state battery 1B shown in Fig. 13(A) and Fig. 13(B) is an example of a thin battery. The solid-state battery 1B has an exterior body 200, and a terminal 210 and a terminal 220 protruding from the exterior body 200 to the outside. The exterior body 200 may be, for example, a film-shaped, bag-shaped, or box-shaped body formed using a material such as resin, ceramic, or insulating-coated metal. The solid-state battery main body 1Ba is accommodated inside the exterior body 200. The solid-state battery 1B may have a structure in which the solid-state battery main body 1Ba coated with a predetermined insulating material (for example, an oxide solid electrolyte) is further coated with the exterior body 200 in a film-shaped, bag-shaped, box-shaped, or other shape.
[0104] The solid-state battery body 1Ba has a positive electrode layer 10, a negative electrode layer 20, and an electrolyte layer 30 provided therebetween. The solid-state battery body 1Ba further has a current collector 40 provided on the positive electrode layer 10, and a current collector 50 provided on the negative electrode layer 20. The electrolyte layer 30, the positive electrode layer 10, the negative electrode layer 20, and the current collector 40 and the current collector 50 of the solid-state battery body 1Ba are made of the same materials as those described for the solid-state battery body 1Aa. A terminal 210 is connected to the current collector 40 on the positive electrode layer 10 side of the solid-state battery body 1Ba by a method such as joining or welding, and a terminal 220 is connected to the current collector 50 on the negative electrode layer 20 side by a method such as joining or welding. The solid-state battery body 1Ba is housed inside the exterior body 200 so that the tips of the terminals 210 and 220 are exposed to the outside.
[0105] In the solid-state battery 1B, the LCPO obtained by the manufacturing method described in the first or second embodiment, that is, the LCPO in which the generation of a different phase is suppressed, is used as the positive electrode active material in the positive electrode layer 10 of the solid-state battery body 1Ba, thereby realizing a high-performance thin solid-state battery 1B with excellent charge / discharge characteristics.
[0106] Fig. 14 is a diagram showing yet another example of the configuration of a solid-state battery. Fig. 14(A) and Fig. 14(B) each show a schematic perspective view of a main part of an example of a solid-state battery. Fig. 14(C) shows a schematic cross-sectional view of a main part of an example of a solid-state battery.
[0107] The solid-state battery 1C shown in FIG. 14(A) is an example of a coin-type or button-type battery, and has a positive electrode layer 10, a negative electrode layer 20, and an electrolyte layer 30 provided therebetween. The solid-state battery 1C may be in a form in which a current collector 40 and a current collector 50 are provided on the positive electrode layer 10 and the negative electrode layer 20, respectively, as shown in FIG. 14(B), for example. The solid-state battery 1C may be covered with a conductive exterior body 201 that is connected to the positive electrode layer 10 (or a current collector provided thereon, not shown) and is not connected to the negative electrode layer 20 (or a current collector provided thereon, not shown), as shown in FIG. 14(C), for example. The electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20, or further the current collector 40 and the current collector 50 of the solid-state battery 1C are made of the same materials as those described for the solid-state battery body 1Aa.
[0108] In the solid-state battery 1C, LCPO obtained by the manufacturing method described in the first or second embodiment, i.e., LCPO in which the generation of a different phase is suppressed, is used as the positive electrode active material for the positive electrode layer 10. This realizes a high-performance coin- or button-type solid-state battery 1C with excellent charge / discharge characteristics.
[0109] The LCPO in which the formation of different phases is suppressed and which is obtained by the production method described in the first or second embodiment can be used not only as a positive electrode active material for the above-mentioned chip-, thin-, coin- or button-type solid-state batteries, but also as a positive electrode active material for batteries of various shapes, such as rectangular or cylindrical.
[0110] In the above description, amorphous LAGP has been exemplified as the oxide solid electrolyte used in the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20. However, the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20 may each contain crystalline LAGP in addition to the amorphous LAGP.
[0111] In the LAGP of the electrolyte layer 30, Li 1.5 Al 0.5 Ge 1.5 (PO4)3 is not limited to the composition, and NASICON-type LAGP of other compositions containing Li 1.4 Al 0.4 Ge 1.6 (PO4)3 may be used. In addition to LAGP, in the electrolyte layer 30, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, garnet-type lithium lanthanum zirconate (Li7La3Zr2O 12 , hereinafter referred to as "LLZ"), perovskite-type lithium lanthanum titanate (Li 0.5 La 0.5 TiO3, hereinafter referred to as "LLT"), partially nitrided lithium phosphate (γ-Li3PO4, hereinafter referred to as "LiPON"), and other oxide solid electrolytes may be used.
[0112] In the positive electrode layer 10 and the negative electrode layer 20, other oxide solid electrolytes such as LAGP, LATP, LLZ, LLT, and LiPON may be used as long as a certain performance is achieved in combination with the active material used.
[0113] For example, in the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20, NASICON-type oxide solid electrolytes represented by the general formula Li 1+u Al u M 2-u (PO4)3 are suitable. Here, the composition ratio u is in the range of 0 < u ≦ 1, and M is one or both of germanium (Ge) and titanium (Ti).
[0114] In the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20, the same type of oxide solid electrolyte may be used for each other, or different types of oxide solid electrolytes may be used for each other. In the electrolyte layer 30, the positive electrode layer 10, and the negative electrode layer 20, one type of oxide solid electrolyte may be used for each, or two or more types of oxide solid electrolytes may be used for each.
Explanation of symbols
[0115] 1A,1B,1C solid state battery 1Aa, 1Ba solid-state battery body 2 Polarity Markers 3,4,5,100 laminate 10 Positive electrode layer 11 Positive electrode layer green sheet 12 Positive electrode layer paste 20 Negative electrode layer 21 Green sheet for negative electrode layer 22 Negative electrode layer paste 30 Electrolyte layer 31 Green sheet for electrolyte layer 32 Substrate for electrolyte layer 33 Electrolyte layer paste 40,50 Current collector 120 Kiln 200, 201 Exterior body 210,220 Terminal
Claims
1. A step of preparing a powder of lithium carbonate, lithium nitrate, or lithium hydroxide in an amount based on the composition of lithium cobalt pyrophosphate, basic cobalt carbonate, cobalt nitrate, cobalt hydroxide, or cobalt oxide, and ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, or phosphoric acid at a first temperature of less than 40° C., and gradually adding water in an amount of 2.0% by weight to 38.3% by weight of the total weight of the powder while mixing the powder at the first temperature to obtain a powdered first material; mixing the first material at a second temperature of 40° C. to 60° C. to obtain a powdered second material; drying the second material at a fourth temperature of 90° C.; Firing the dried second material in an air atmosphere or a non-oxidizing atmosphere at a third temperature of 650° C. to 690° C.; A method for producing lithium cobalt pyrophosphate, comprising:
2. the first material comprises lithium phosphate; 2. The method of claim 1, wherein the second material comprises ammonium cobalt phosphate.
3. A step of preparing a powder of lithium carbonate, lithium nitrate or lithium hydroxide in an amount based on the composition of lithium cobalt pyrophosphate, basic cobalt carbonate, cobalt nitrate, cobalt hydroxide or cobalt oxide, and ammonium dihydrogen phosphate, ammonium monohydrogen phosphate or phosphoric acid at a first temperature of less than 40°C, and gradually adding water in an amount of 14.9% by weight to 95.8% by weight of the total weight of the powder and mixing the powder at a second temperature of 40°C to 60°C to obtain a powdered first material; drying the first material at a fourth temperature of 90° C.; Firing the dried first material in an air atmosphere or a non-oxidizing atmosphere at a third temperature of 650° C. to 690° C.; A method for producing lithium cobalt pyrophosphate, comprising:
4. 4. The method of claim 3, wherein the first material includes lithium phosphate and ammonium cobalt phosphate.
5. forming a positive electrode active material comprising lithium cobalt pyrophosphate; forming a laminate having a positive electrode layer including the positive electrode active material, a negative electrode layer, and an electrolyte layer provided between the positive electrode layer and the negative electrode layer; Firing the laminate; Including, The step of forming the positive electrode active material includes: A step of preparing a powder of lithium carbonate, lithium nitrate, or lithium hydroxide, basic cobalt carbonate, cobalt nitrate, cobalt hydroxide, or cobalt oxide, and ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, or phosphoric acid in an amount based on the composition of the lithium cobalt pyrophosphate, at a first temperature of less than 40° C., and gradually adding and mixing water in an amount of 2.0% by weight to 38.3% by weight of the total weight of the powder at the first temperature, thereby obtaining a powdered first material; mixing the first material at a second temperature of 40° C. to 60° C. to obtain a powdered second material; drying the second material at a fourth temperature of 90° C.; Firing the dried second material in an air atmosphere or a non-oxidizing atmosphere at a third temperature of 650° C. to 690° C.; A method for producing a solid-state battery comprising the steps of:
6. forming a positive electrode active material comprising lithium cobalt pyrophosphate; forming a laminate having a positive electrode layer including the positive electrode active material, a negative electrode layer, and an electrolyte layer provided between the positive electrode layer and the negative electrode layer; Firing the laminate; Including, The step of forming the positive electrode active material includes: A step of preparing a powder of lithium carbonate, lithium nitrate, or lithium hydroxide in an amount based on the composition of the lithium cobalt pyrophosphate, basic cobalt carbonate, cobalt nitrate, cobalt hydroxide, or cobalt oxide, and ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, or phosphoric acid at a first temperature of less than 40°C, and gradually adding water in an amount of 14.9% by weight to 95.8% by weight of the total weight of the powder and mixing the powder at a second temperature of 40°C to 60°C to obtain a powdered first material; drying the first material at a fourth temperature of 90° C.; Firing the dried first material in an air atmosphere or a non-oxidizing atmosphere at a third temperature of 650° C. to 690° C.; A method for producing a solid-state battery comprising the steps of:
Citation Information
Patent Citations
Transition metal complex hydroxide suitable for precursor of positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, and nonaqueous electrolyte secondary battery comprising the positive electrode active material
JP2012252844A
Method for manufacturing positive electrode substance material for all-solid battery, and positive electrode active substance material for all-solid battery
JP2017182949A
Method for manufacturing all-solid battery
JP2018037341A
Manufacturing method of positive electrode active material
JP2019149302A
Method for producing lithium cobalt pyrophosphate, and method for producing lithium cobalt pyrophosphate-carbon complex
WO2020031690A1